2014
DOI: 10.1007/s13197-014-1327-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transglutaminase on quality characteristics of a value-added product tilapia wastes

Abstract: The aim of this work was to evaluate the physicochemical, instrumental color and texture, and sensory qualities of restructured tilapia steaks elaborated with small sized (noncommercial) tilapia fillets and different levels of microbial transglutaminase (MTG). Four concentrations of MTG were used: CON (0 % MTG), T1 (0.1 % MTG), T2 (0.5 % MTG), and T3 (0.8 % MTG). In addition, bacterial content and pH shifts were also evaluated during 90 days of frozen storage. The different levels of MTG did not affect (P>0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Similarly, Cofrades et al (2011) reported that the cooking process decreased redness and increased lightness and yellowness in restructured poultry meat, resulting in a whiter coloration. Monteiro et al (2015a) also observed that the cooking procedure increased the lightness and yellowness values, while decreasing the redness of restructured tilapia steaks, in agreement with the present findings.…”
Section: Statistical Analysessupporting
confidence: 92%
“…Similarly, Cofrades et al (2011) reported that the cooking process decreased redness and increased lightness and yellowness in restructured poultry meat, resulting in a whiter coloration. Monteiro et al (2015a) also observed that the cooking procedure increased the lightness and yellowness values, while decreasing the redness of restructured tilapia steaks, in agreement with the present findings.…”
Section: Statistical Analysessupporting
confidence: 92%
“…The concentrations used for the restructured fish products (Table 1) were defined based on the studies of Maia et al (2015) for galactomannan, and Monteiro et al (2015) for transglutaminase (Control).…”
Section: Materiais and Methodsmentioning
confidence: 99%
“…Microbial transglutaminase (MTGase, EC 2.3.2.13), a calcium‐independent enzyme, has been widely used to improve the gelation properties of varying surimi types (Lee & Park, ; Monteiro et al, ; Moreno, Cardoso, Solas, & Borderias, ; Uresti, Velazquez, Vázquez, Ramírez, & Torres, ). MTGase catalyzes the transfer of γ‐carboxyamide groups of glutaminyl residues in proteins to the ε‐amino groups of lysyl residues.…”
Section: Introductionmentioning
confidence: 99%